2017
DOI: 10.21276/ijlssr.2017.3.3.22
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Insulin Resistance and its Association with Obesity and Alcoholism in Male Medical Students of Bhopal

Abstract: ABSTRACT-Background: Obesity is rising in medical students due to their stressful academic calendar and sparse time for sports. Obesity is aggravated by the regular drinking of alcohol, a recreational and stress-busting activity, particularly for the male students. Obesity leads to insulin resistance. Homeostasis model assessment-estimated insulin resistance (HOMA-IR) >2 has been reported to independently predict cardiovascular risk. Although many studies are there on obesity of medical students, few studies e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Similar result was observed in a study conducted by Charpe C et al in which 40% of the students showed IR. [23] Many studies have shown that IR precedes and is considered as a strong predictor for development of DM. Hence, estimation of IR by HOMA-IR serves as the surrogate marker towards early detection of DM and associated comorbidities even before the actual disease sets in.…”
Section: Discussionmentioning
confidence: 99%
“…Similar result was observed in a study conducted by Charpe C et al in which 40% of the students showed IR. [23] Many studies have shown that IR precedes and is considered as a strong predictor for development of DM. Hence, estimation of IR by HOMA-IR serves as the surrogate marker towards early detection of DM and associated comorbidities even before the actual disease sets in.…”
Section: Discussionmentioning
confidence: 99%
“…WC>= 90cm is therefore a strong indication for screening students for insulin resistance to prevent future complications. [20] This study emphasizes the need for early identification of the risk factors leading to excessive BMI, body fat% and initiation of preventive measures in order to prevent the deterioration of cardiovascular performance in 11 to <13 years old school going Bengali boys. [21] The methodological analysis on obesity clearly indicates that prevention is better than cure.…”
Section: Glycemic Load (Gl)-mentioning
confidence: 99%
“…The percentage of overweight and obese children and adolescents has been increasing in India. Research studies done on children and adolescents by Kotian et al (9.9%) [3] ; Stigler (16.6%) [4] ; Gupta et al (11.7%) [5] ; Raj (40%) [6] and Bharati et al (3.1%) [7] reported varied prevalence rates of overweight and obesity in different parts of India. Based on data from the NFHS-3 [8] and NFHS-4 [9] , the percentage of adolescents and adults between the ages of 15 and 49 who were overweight or obese has doubled from 9.3% to 18.6% among males and 12.6% to 20.7% among females.…”
Section: Prevalence Of Overweight and Obesity Among Adolescentsmentioning
confidence: 99%